Leveling the Playing Field: A New Proposed Method to Address Relative Age- and Maturity-Related Bias in UK Male Academy Soccer Players - Bolckmans, Sofie; Starkes, Janet L.; Towlson, Chris; Barnes, Chris; Parkin, Guy; Helsen, Werner F. (Frontiers in Sports and Active Living, 2022)
Relative age selection bias persists within all major soccer leagues and youth soccer academies across the globe, with the relative age effect (RAE) being typically characterized as the over selection of relatively older players. The aim of this study was to examine if a new allocation method (Helsen et al., 2021) i) eliminates the RAE, and ii) reduces the presence of any additional maturity-related differences in anthropometric and physical fitness characteristics which may exist between players within the same selection category. In the first phase, 1003 academy soccer players (under (U) 9-16) from 23 UK professional soccer clubs were sampled and a clear RAE per birth quarter (Q) was observed for the overall sample (Q1= 45.0% vs Q4= 9.8%) as well as for the different age categories. Using the newly suggested recategorization method, youth players were divided by allocation date which was defined as the midway point between the chronological age and the estimated developmental (ED) birthdate. After reallocation of the players using ED, the distribution of players was equally spread (Q1= 25.3%, Q2= 25.6%, Q3= 22.4%, Q4= 26.7%). After allocation, the mean stature was reduced by 16.6cm (from 40.3± 7.08 to 23.7± 4.09cm, d= 2.87). Mean body mass difference after allocation was reduced by 6.7kg (from 33.2± 6.39 to 26.5± 4.85 kg, d= 1.18). 42.7% of the sample would have been reallocated to a different age group compared to the current one. After reallocation, 45.0% of the anthropometric and physical fitness comparisons showed reductions in the within-group variation expressed as a percentage of coefficient of variation (CV%). By eliminating both the RAE and reducing temporary maturity-related anthropometric and physical fitness differences, soccer academies across the world may diversify and increase the size of the talent pool both for clubs and national youth teams. In conclusion, this study provides further evidence that the newly proposed allocation method possesses the potential to remove the RAE and creates a more ‘leveled playing field’ by reducing the within-group variation of anthropometric and physical fitness characteristics affording relatively younger and, eventually, late-maturing players the opportunity to develop their talent in a fair way.